2022
DOI: 10.4103/kkujhs.kkujhs_12_22
|View full text |Cite
|
Sign up to set email alerts
|

Women's Awareness and Rate of the Use of Contraception in the Kingdom of Saudi Arabia

Abstract: Background: The prevention of unplanned pregnancies brings many benefits for women and their families alike, as well as for society in general. However, recent statistics indicate a need for increased knowledge and use of contraception in addition to the introduction of educational family planning services in the countries of the Middle East. Objectives: This review sought to explore women's awareness and rates of contraceptive use in the Kingdom of Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…According to post hoc analysis, IUD users had significantly higher overall QoL than people who used natural techniques (M=50, SD=9.0, p>0.01) (M=55.7, SD=9.6, respectively) [38]. In addition, a systematic review of thirteen research demonstrated that awareness of and usage of contraception in KSA were at relatively low levels [39]. Similarly, 75% of women in Sabya City_Jazan, Saudi Arabia, used contraceptives regularly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to post hoc analysis, IUD users had significantly higher overall QoL than people who used natural techniques (M=50, SD=9.0, p>0.01) (M=55.7, SD=9.6, respectively) [38]. In addition, a systematic review of thirteen research demonstrated that awareness of and usage of contraception in KSA were at relatively low levels [39]. Similarly, 75% of women in Sabya City_Jazan, Saudi Arabia, used contraceptives regularly.…”
Section: Literature Reviewmentioning
confidence: 99%